Employee Performance and Knowledge Management in a Manufacturing Company: Internal and External Factors to Consider - Amanda Rahadian, Faika (Dinasti Publisher, 2023)
Manufacturing firms play an important economic role by producing necessary goods and services. Manufacturing organizations must constantly enhance their operations and processes to remain competitive in today's global market. One method is to concentrate on staff performance and knowledge management practices. Many manufacturing organizations, however, struggle to identify the elements that influence these sectors. This study sought to fill this void by identifying internal and external factors influencing employee performance and knowledge management practices in a manufacturing organization. The study employed a mixed-methods strategy to gather and analyze data, including surveys, interviews, and case studies. Data from employees and managers in a manufacturing company were collected and analyzed using qualitative and quantitative approaches. This study examined the elements influencing employee performance and knowledge management practices in a manufacturing company context, drawing on prior research and fresh data. This study's conclusions are essential for industrial organizations looking to enhance their operations and processes and university scholars studying staff performance and knowledge management. This study can assist manufacturing businesses in developing successful strategies for increasing employee performance and knowledge management practices by identifying the crucial elements that influence these areas.